Yo! Narratividade urbana: os gritos da periferia - Silva, Raquel Bevilaqua da (2005)
The present study analyzes three musical texts by the Hip-Hop group Racionais MC s, from the periphery of São Paulo under the discursive view. We have selected in these texts cuttings referring to the way the rapper, inhabitant of the periphery, interpolates another subject, also inhabitant of this space, for him to identify himself to the rules which govern life of groups from the periphery. Furthermore, we work with the hypothesis that the investigated conduct rules constitute two opposing discursive universes, the Good one and the Bad one. In the first one, would be those inhabitant of the periphery who obey to the socially instituted rules; in the second one, would be all the other subjects, considered enemies of the periphery group (white subjects with superior acquisition power, black subjects who do not follow the rules of the periphery). This way, the rapper opposes his universe (the Good one) to the universe of other subjects (the Bad one). However, we observe that the Bad universe leaves signs in the formulation of the rapper s saying. These signs are discursive marks which we aim at identifying and analyzing, making relations to linguistic and discursive elements in which we consider the approaches of the postmodern society with its social inclusion/exclusion process, of the working of the juridical and political spheres in this society and its relation to the formulation of the rapper s saying.